INCREASING THE EFFICIENCY OF WORKING WITH PROBLEM LOANS IN BANKS - Makhamadumarov Kasimjon Dilmurod ugli (American Journals, 2024)
Problem loans, also known as non-performing loans (NPLs), pose a significant risk to the financial stability of banks and financial institutions. Efficiently managing these problematic assets is crucial for maintaining the health of a bank's portfolio and ensuring overall financial stability. This article explores various strategies to enhance the efficiency of working with problem loans, including early identification and monitoring, restructuring and refinancing, establishing dedicated problem loan units, leveraging legal and regulatory frameworks, enhancing communication with borrowers, utilizing technology and data analytics, and forming partnerships and outsourcing. Through detailed analysis and case studies from past financial crises, this article provides a comprehensive overview of best practices and methodologies that banks can adopt to mitigate the risks associated with NPLs, ultimately contributing to the resilience of the financial system.
Keywords: Non-Performing Loans (NPLs). Problem Loans. Financial Stability. Loan Restructuring. Early Warning Systems. Loan Monitoring. Credit Risk Management. Financial Institutions. Debt Recovery. Banking Crisis. Economic Downturns. Loan Refinancing. Data Analytics. Legal and Regulatory Compliance. Financial Counseling. Loan Management Strategies.